Neonatal Adrenal Hemorrhage: A Case Series - Tognato, Eleonora; Ceratto, Simone; Enrico, Giorgia; Fiorica, Lorenzo; Spola, Roberta; Loperfido, Bruna; Cimminelli, Lina; Militello, Maria A.; Eshraghy, Mohammad R.; Savino, Francesco; Giuliani, Francesca; Perona, Anna; Manzoni, Paolo (American Journal of Perinatology, 2020)
Neonatal adrenal hemorrhage (NAH) in newborn infants is a rare event that is associated with specific anatomical and vascular characteristics. It is more common in term infants and occurs more often in neonates who feature perinatal asphyxia. Symptoms that more frequently prompt to diagnosis are prolonged jaundice, detection of an abdominal mass, anemia, scrotal discoloration and/or swelling, hypotonia, lethargy, and hypertension. However, NAH may also occur without symptoms with its detection being occasional. Imaging through ultrasound scans is the cornerstone of diagnosis and follow-up monitoring over time. Here we report on a small NAH case series comprising three full-term, macrosomic infants who were born by vaginal delivery. The first and second ones showed clear signs of birth asphyxia, whereas the third was completely asymptomatic. In all three patients, only the right adrenal gland was involved, in line with what happens in 70% of cases. NAH is usually self-limiting and prone to a progressive resolution in a time ranging between 3 weeks and 6 months and so did in our three patients.Key Points
Keywords: neonatal adrenal hemorrhage; macrosomia; vaginal delivery; abdominal ultrasound